On "place" and "character" in architecture : the case of Porto Alegre, south Brazil - Fiore, Renato Holmer (2000)
The present work is a study on "place character" in architecture, analysed in relation to specific cases of Porto Alegre, capital of Rio Grande do Sul (Brazil). "Locality" has frequently been a central issue in discourses about formal quality in architecture. Architectural artifacts are commonly understood, aesthetically, in relation to their place and context. This issue, however, involves different aspects, and may be interpreted in different ways, being also connected to discussions about "national" or "regional character''. The first two chapters of the thesis discuss existing VIews and forrnulations concerning the subject we describe as "architectural place character", with a review of contributions from main intemational ( chiefly European) and local 20th century architectural writers. Aiming at developing a renewed investigation of the subject, the subsequent chapters analyse cases from Porto Alegre. An apparently chaotic city, with a relatively short and little preserved past, and where different foreign influences play important roles, Porto Alegre appears as a problematic situation especially from the viewpoint of propositions which are principally European in origin, and have tended to concentrate on cases usually regarded as being of high quality or representing a strong local, national or regional, character. The specific cases analysed are places/buildings which are significant in the city's image, structure and life, and represent different situations from which to look at architectural place character. They include both modem and historicist architecture, monumental architecture and "utilitarian" structures, and also open, urban space. The analyses concentrate on forrna1/aesthetic significance at a public levei, and make use of forms of representation of the objects of study in the press, observing the historical processes through which place character is generated, changed, and understood. The result of the analysis is to demonstrate that place character, instead of being a fixed value, is fundamentally contingent on historical circumstances, and therefore changeable.